Eeny, meeny, miney mole - Yolen, Jane (New York : Voyager Books/Harcourt Brace & Company, 1992)
Three moles live underground, and then one of them finally ventures upward to find out what the world is like "Up Above".
Keywords: Mole (Animals)-Fiction